Panax notoginseng saponins inhibits NLRP3 inflammasome-mediated pyroptosis by downregulating lncRNA-ANRIL in cardiorenal syndrome type 4 - Ying Xu; Luxi Cao; Wenli Zou; Rizhen Yu; Wei Shen (BMC, 2023)
Abstract Objective Cardiorenal syndrome type 4 (CRS4) is a complication of chronic kidney disease. Panax notoginseng saponins (PNS) have been confirmed to be efficient in cardiovascular diseases. Our study aimed to explore the therapeutic role and mechanism of PNS in CRS4. Methods CRS4 model rats and hypoxia-induced cardiomyocytes were treated with PNS, with and without pyroptosis inhibitor VX765 and ANRIL overexpression plasmids. Cardiac function and cardiorenal function biomarkers levels were measured by echocardiography and ELISA, respectively. Cardiac fibrosis was detected by Masson staining. Cell viability was determined by cell counting kit-8 and flow cytometry. Expression of fibrosis-related genes (COL-I, COL-III, TGF-β, α-SMA) and ANRIL was examined using RT-qPCR. Pyroptosis-related protein levels of NLRP3, ASC, IL-1β, TGF-β1, GSDMD-N, and caspase-1 were measured by western blotting or immunofluorescence staining. Results PNS improved cardiac function, and inhibited cardiac fibrosis and pyroptosis in a dose-dependent manner in model rats and injured H9c2 cells (p < 0.01). The expression of fibrosis-related genes (COL-I, COL-III, TGF-β, α-SMA) and pyroptosis-related proteins (NLRP3, ASC, IL-1β, TGF-β1, GSDMD-N, and caspase-1) was inhibited by PNS in injured cardiac tissues and cells (p < 0.01). Additionally, ANRIL was upregulated in model rats and injured cells, but PNS reduced its expression in a dose-dependent manner (p < 0.05). Additionally, the inhibitory effect of PNS on pyroptosis in injured H9c2 cells was enhanced by VX765 and reversed by ANRIL overexpression, respectively (p < 0.05). Conclusion PNS inhibits pyroptosis by downregulating lncRNA-ANRIL in CRS4.